2018
DOI: 10.1016/j.carbon.2017.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Determinant influence of the electrical conductivity versus surface area on the performance of graphene oxide-doped carbon xerogel supercapacitors

Abstract: A series of resorcinol formaldehyde based carbon xerogels were synthesized under identical conditions using different graphene oxide loads. The gelification reaction was carried out using a stable aqueous suspension of graphene oxide, yielding organic gels with graphene oxide concentrations ranging from 1.2 to 2.5%. After the carbonization, xerogels with medium surface area (650 m 2 /g) and a highly improved electrical conductivity were obtained. Specific capacitance of 120 F/g of one electrode at very high sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…ESR of HPC‐0, HPC‐5, HPC‐10, and HPC‐15 are almost identical (within experimental error) in two different solutions (Table S2). ESR varies around 0.5 Ω in both solutions, which is considered quite low, thus highlighting the consistency of electrode performance and the practical applicability of the synthesis route we reported here (Table S2) . In the medium to high frequency region, small semicircle arc appears in HPC‐5, HPC‐10, and HPC‐15 cases in both solutions, which corresponds to the presence of R ct at the electrode|electrolyte interface (insets of Figure (a) and Figure (b)) .…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…ESR of HPC‐0, HPC‐5, HPC‐10, and HPC‐15 are almost identical (within experimental error) in two different solutions (Table S2). ESR varies around 0.5 Ω in both solutions, which is considered quite low, thus highlighting the consistency of electrode performance and the practical applicability of the synthesis route we reported here (Table S2) . In the medium to high frequency region, small semicircle arc appears in HPC‐5, HPC‐10, and HPC‐15 cases in both solutions, which corresponds to the presence of R ct at the electrode|electrolyte interface (insets of Figure (a) and Figure (b)) .…”
Section: Resultssupporting
confidence: 62%
“…ESR varies around 0.5 Ω in both solutions, which is considered quite low, thus highlighting the consistency of electrode performance and the practical applicability of the synthesis route we reported here (Table S2). [52] In the medium to high frequency region, small semicircle arc appears in HPC-5, HPC-10, and HPC-15 cases in both solutions, which corresponds to the presence of R ct at the electrode j electrolyte interface (insets of Figure 6(a) and Figure 6(b)). [53] HPC-10 clearly has the lowest R ct among the four HPCs samples in both 1 M H 2 SO 4 and 6 M KOH (Table S2), which correlates with its highest specific capacitance and performance retention.…”
Section: Electrochemical Performancesmentioning
confidence: 91%
“…The specific capacitance of O‐D‐CNT@RFC, calculated at a current density of 0.5 A g −1 , is higher than that of GO‐embedded carbon xerogels synthesized from aqueous conditions reported by Gloria Ramos‐Fernández, where the polymerization of resorcinol and formaldehyde is carried out using a aqueous suspension of graphene oxide as reaction medium. After steam activation, the resultant activated GO‐embedded carbon xerogel delivers a specific capacitance of 160 F g −1 at a current density of 0.1 A g −1 . The capacitance of O‐D‐CNT@RFC is also superior to that of carbon aerogels prepared though supercritical drying followed by HNO 3 oxidation, which generates a RF‐based carbon aerogels with a specific capacitance of 124 F g −1 at a current density of 0.5 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The electrical conductivity of the RF based carbon aerogels plays a key role in their electrochemical performances, such as energy density, charge transfer resistance, cyclic stability, and energy efficiency . A few recent works even demonstrated that the electrical conductivity, rather than the surface area, is the determinant to the final supercapacitor performances of the RF carbon aerogels . Carbon nanotubes (CNT) possess an ordered hollow nanostructure exclusively composed of graphitic carbon sheets which endows the CNT with extremely high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation